2020 IEEE International Conference on Industrial Technology (ICIT) 2020
DOI: 10.1109/icit45562.2020.9067101
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Approach to Dynamic Behavior in Electrical Lines Used for Well Intervention Tools

Abstract: Electrical lines, also known as wirelines, are commonly used for well intervention techniques to increase flow of oil and gas wells that can be executed during a low service time. Previous studies show the importance of this electrical conductor for power delivery as well as communication purposes. Nevertheless, a validated model and its parameters of this channel are still missing. This papers outlines a geometrical approach to estimate the electrical dynamic behavior for wireline types used in the field with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…This same cable is the connection for power to, and communication with the tool. The usable bandwidth of this cable is heavily reduced by the length [1], [2]. It is found that the cable exhibits a bandiwdth up to approx.…”
Section: Introductionmentioning
confidence: 97%
“…This same cable is the connection for power to, and communication with the tool. The usable bandwidth of this cable is heavily reduced by the length [1], [2]. It is found that the cable exhibits a bandiwdth up to approx.…”
Section: Introductionmentioning
confidence: 97%